Interaction between genetics and the adherence to the Mediterranean diet: the risk for age-related macular degeneration. Coimbra Eye Study Report 8 - Barreto, Patrícia (2023)
Background Age-related macular degeneration (AMD) is a multifactorial degenerative disease of the macula. Different factors, environmental, genetic and lifestyle, contribute to its onset and progression. However, how they interconnect to promote the disease, or its progression, is still unclear. With this work, we aim to assess the interaction of the genetic risk for AMD and the adherence to the Mediterranean diet in the Coimbra Eye Study. Methods Enrolled subjects (n = 612) underwent ophthalmological exams and answered a food questionnaire. Adherence to the Mediterranean diet was assessed with mediSCORE. An overall value was calculated for each participant, ranging from 0 to 9, using the sum of 9 food groups, and a cut off value of ≥ 6 was considered high adherence. Rotterdam Classification was used for grading. Participants’ genotyping was performed in collaboration with The European Eye Epidemiology Consortium. The genetic risk score (GRS) was calculated for each participant considering the number of alleles at each variant and their effect size. Interaction was assessed with additive and multiplicative models, adjusted for age, sex, physical exercise, and smoking. Results The AMD risk was reduced by 60% in subjects with high adherence to the Mediterranean diet compared to subjects with low adherence to the Mediterranean diet. Combined effects of having low adherence to the Mediterranean diet and high GRS led to almost a 5-fold increase in the risk for AMD, compared to low GRS and high adherence to the Mediterranean diet. The multiplicative scale suggested a multiplicative interaction, although not statistically significant [odds ratio (OR) = 1.111, 95% CI 0.346–3.569, P = 0.859]. The additive model showed a causal positive effect of the interaction of GRS and adherence to the Mediterranean diet: relative excess risk due to interaction (RERI) = 150.9%, (95% CI: − 0.414 to 3.432, P = 0.062), attributable proportion due to interaction (AP) = 0.326 (95% CI: − 0.074 to 0.726, P = 0.055) and synergy index (SI) = 1.713 (95% CI: 0.098–3.329, P = 0.019). High GRS people benefited from adhering to the Mediterranean diet with a 60% risk reduction. For low-GRS subjects, a risk reduction was also seen, but not significantly. Conclusions Genetics and Mediterranean diet interact to protect against AMD, proving there is an interplay between genetics and environmental factors.